2018
DOI: 10.1149/2.0211802jes
|View full text |Cite
|
Sign up to set email alerts
|

Raman and Electrochemical Study of Zirconium in LiCl-KCl-LiF-ZrCl4

Abstract: In this work, Raman measurements were performed with quenched LiCl-KCl-LiF-ZrCl 4 /ZrF 4 /K 2 ZrF 6 salt mixtures for deciphering the coordination chemistry of zirconium(IV) in the presence of fluoride ion in the melt. The occurrence of ZrCl 6 2− , ZrCl 4 F 2 2− , ZrF 6 2− , ZrF 7 3− and ZrF 8 4− in melt at different F/Zr molar ratios was confirmed by Raman spectra. The electrochemical redox behaviors of zirconium in LiCl-KCl-LiF-ZrCl 4 were also examined at 773 K. Transient methods such as cyclic voltammetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…They assigned those peaks to the octahedral ZrCl 6 2− structure with two Raman-active vibration modes (T 2g and A 1g ). 44…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They assigned those peaks to the octahedral ZrCl 6 2− structure with two Raman-active vibration modes (T 2g and A 1g ). 44…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al 44 observed Raman peaks at similar wavenumbers (163 cm −1 and 332 cm −1 ) in the spectrum of Raman-active vibration modes (T 2g and A 1g ). 44 Previous studies 42,[45][46][47][48][49] peaks in the O4 agglomerate relative to the background noise (zone A in Fig. 9) were noticeably greater than those of ZrCl 4 (5.0 wt%)-LiCl-KCl.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 89%
“…Consequently, the Ln−F interaction was anticipated to be less strong than others. Furthermore, for M n+ with high polarizing power, [MF x ] n−x (x=6‐8) species were determined with the addition of fluoride in molten chloride salts, which indicated the complete substitution of F − for Cl − in the first coordination sphere [5a,c,g,h,13] . Since ionic bonding model also gave the best interpretation of M−F interaction, [21] the remarkable difference between Ln and M species in molten chloride‐fluoride salts should be attributed to the discrepancy in polarizing power.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its excellent corrosion-resistance and extremely low neutron-adsorption cross-section, zirconium has been widely used in nuclear industry. [3] In FLiBe-ZrF 4 -UF 4 or LiF-ZrF 4 -ThF 4 , ZrF 4 is used for stabilizing the uranium/thorium species against the oxygenation by complexing with oxygen. [4] In addition, Zr(IV) can be used as a substitute for Th(IV) in routine research to avoid the radioactivity based on their chemical similarities.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Based on the results of previous studies by means of spectroscopic techniques, zirconium fluoride anions were considered probably to exist in the form of these three types ZrF 6 2À , ZrF 7 3À and ZrF 8 4À in fluorine molten salt and chlorine molten salt with K 2 ZrF 6 and/or LiF as fluorine source at proper F/Zr molar ratios. [3,8] In order to investigate the energy and structural properties, vibrational frequencies of ZrF n (nÀ 4)À anions were determined with ab initio and density functional theory (DFT) calculations. [10] In addition, the quantitative analysis has also been performed on the structure of ZrF 4 in molten alkali fluorides with EXAFS and MD.…”
Section: Introductionmentioning
confidence: 99%